CIPP Evaluation of English Language Teaching for Deaf Students in the Bengkala Deaf Inclusive Education Program - I Putu Gede Pasek Pastika; Made Hery Santosa; Kadek Sintya Dewi (Journal of Educational Study, 2026)
This study evaluated the implementation of English teaching and learning for deaf students in the Bengkala Deaf Inclusive Education (BDIE) program at SDN 2 Bengkala, Bali, Indonesia. Guided by the Context, Input, Process, and Product (CIPP) evaluation model, the study employed a qualitative program evaluation design to examine the implementation and effectiveness of inclusive English language education. Data were collected through semi-structured interviews with the school principal, English teacher, homeroom teachers, sign language teacher, and deaf students, as well as non-participant classroom observations. Data were analyzed using Miles et al.’s Interactive Model of Analysis and thematic analysis.The findings indicate that the BDIE program has established a strong foundation for inclusive English education through a supportive community culture that promotes the acceptance of deaf students and the use of sign language. However, the program's effectiveness is constrained by limited specialized resources, including the shortage of trained personnel, insufficient professional development, and inadequate communication support during English instruction. Although visually oriented teaching strategies and sign language mediation facilitated students’ vocabulary acquisition and basic literacy skills, learning outcomes remained limited by restricted instructional time and insufficient learning support beyond the classroom. The study concludes that strengthening institutional support, teacher capacity, and communication accessibility is essential for improving the quality and sustainability of inclusive English education for deaf learners.